EVALUASI KEBIJAKAN PROFRAM KOTAKU DALAM PENCEGAHAN DAN PENINGKATAN KUALITAS PERMUKIMAN KUMUH DAN PERUMAHAN KUMUH DI KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN - eki aditia putra; Karjuni Dt Maani (Jurusan Ilmu Administrasi Negara, 2024)
This research investigates the Evaluation of the Kotaku Program Policy in Preventing and Improving the Quality of Slum Settlements and Slum Housing in Central Pariaman District, Pariaman City. The research was motivated by the sub-optimal implementation of the Kotaku program and the condition of the drainage channels which were not maintained, as seen by the large amount of rubbish, water not flowing, and damaged channel stones. The research method uses a qualitative approach with descriptive methods and purposive sampling techniques. The results of the research show that the condition of the road, which was originally intended for pedestrians but is often used by motorbikes, has caused problems of damage and poor maintenance on the roads around the river. The drainage is also not well maintained, due to lack of supervision, and there is still a lot of rubbish in it, causing an unpleasant odor. The problem of full trash bins and lack of supervision from the Kotaku team illustrates the need to improve the effectiveness of this program. Better collaboration between the Kotaku team, local government and communities is needed to create a cleaner and healthier environment. Thus, improving infrastructure and stricter supervision are the keys to increasing the success of the Kotaku Program in improving the conditions of slum settlements and the surrounding environment.